AN ANALYSIS OF STUDENTS’ GRAMMATICAL ERROR IN ARGUMENTATIVE WRITING - Puspita, Ai Tita (IPI Garut Press, 2021)
This study is entitled “An Analysis of Students’ Grammatical Error in Argumentative Writing”. The objective of this study is to identify what types of grammatical errors mostly made by students in argumentative writing based on Dulays’s surface strategy taxonomy (1982). The students sometimes make errors on the use of grammar when they produce an English writing, also in argumentative writing. It is because Indonesian and English have their own grammatical system. In order to obtain valid findings, qualitative method was used in this study. Six (6) argumentative writing were collected from 6 students in the second semester. Based on the error analysis conducted, the researcher found that errors regarding auxiliary and wrong form of words were the most dominant errors in misformation which consisted of 22 errors. Then it is followed by omission errors consisted of 6 errors and the dominant grammatical error done by the students was omitting the auxiliary. Addition and misordering were only found 1 error from each of them. The findings indicate that the students have difficulties in using correct form, especially in misformation of suffix –s/ -es/ -ed/ -ing. This problem may occur due to their lack of knowledge of English grammatical rules.